OPTIMALISASI LAMA PROSES PENGEMBUNAN DAN PENGARUHNYA TERHADAP KUALITAS MADU TESSO NILO DI DESA SUNGAI PAGAR KECAMATAN KAMPAR KIRI HILIR KABUPATEN KAMPAR - Nurlistiani Fitrianingsih; Defri Yoza; Rudianda Sulaeman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Honey is one of the non-timber forest products that come from animals that are still alive who have the potential to be developed and cultivated. Honey is the natural sweet substance produced by bees with the nectar of flowers raw materials. The high demand for honey at this time, affect the increase in the occurrence of counterfeit or honey products that do not pay attention to the quality of honey Indonesian National Standard ( SNI ), related to honey quality standards set by the government. The quality standards of honey in Indonesia, especially for commercial purposes, refers to the SNI 01-3545-2004. The water content of a maximum of 22 % honey, glucose content of at least 65 % b/b and the sucrose content of up to 5 % b/b.Honey processing naturally without adding chemicals to preserve the quality of honey is needed, but the treatment process takes quite a long time with limited capacity. Processing herein used is a decrease in water content by means of condensation. This study aims to determine the length of the condensation process effectively and efficiently without reducing the quality or the quality of honey with honey quality in accordance with the provisions of SNI has been determined. This study used an experimental method which consisted of 5 treatments and 3 replications, the treatment is a long process of condensing 06 hours, 12 hours, 18 hours, 24 hours and 30 hours. The results showed that long condensing 18 hours are the best results in maintaining the quality of honey, with the results of the water content of 20.33 %, 91.36 % of the content of glucose and sucrose content of 3.83%. Keywords: Honey , honey quality , condensation